Advances in Magnetic Nanomaterials and Nanostructures - Francesco Congiu; Giorgio Concas (Magnetochemistry)
Magnetic nanomaterials, in which non-bulk magnetic properties emerge because of their low dimension, are a class of materials with huge application potential in several areas, providing, at the same time, an exciting field of fundamental research [...]